Prevalence and correlates of treatment failure among Kenyan children hospitalised with severe community‐acquired pneumonia: a prospective study of the clinical effectiveness of WHO pneumonia case management guidelines. Issue 11 (14th August 2014) - Agweyu, Ambrose; Kibore, Minnie; Digolo, Lina; Kosgei, Caroline; Maina, Virginia; Mugane, Samson; Muma, Sarah; Wachira, John; Waiyego, Mary; Maleche‐Obimbo, Elizabeth
Abstract Objective To determine the extent and pattern of treatment failure (TF) among children hospitalised with community‐acquired pneumonia at a large tertiary hospital in Kenya. Methods We followed up children aged 2–59 months with WHO‐defined severe pneumonia (SP) and very severe pneumonia (VSP) for up to 5 days for TF using two definitions: (i) documentation of pre‐defined clinical signs resulting in change of treatment (ii) primary clinician's decision to change treatment with or without documentation of the same pre‐defined clinical signs. Results We enrolled 385 children. The risk of TF varied between 1.8% (95% CI 0.4–5.1) and 12.4% (95% CI 7.9–18.4) for SP and 21.4% (95% CI 15.9–27) and 39.3% (95% CI 32.5–46.4) for VSP depending on the definition applied. Higher rates were associated with early changes in therapy by clinician in the absence of an obvious clinical rationale. Non‐adherence to treatment guidelines was observed for 70/169 (41.4%) and 67/201 (33.3%) of children with SP and VSP, respectively. Among children with SP, adherence to treatment guidelines was associated with the presence of wheeze on initial assessment (P = 0.02), while clinician non‐adherence to guideline‐recommended treatments for VSP tended to occur in children with altered consciousness (P < 0.001). Using propensity score matching to account for imbalance in the distribution of baseline clinical characteristics among children with VSP revealed no difference in TF between those treated with the guideline‐recommended regimen vs. more costly broad‐spectrum alternatives [risk difference 0.37 (95% CI −0.84 to 0.51)]. Conclusion Before revising current pneumonia case management guidelines, standardised definitions of TF and appropriate studies of treatment effectiveness of alternative regimens are required.